Manual and automated synthesis of modified oligonucleotides on core–shell solid supports - Luis M. Menéndez-Méndez; Carme Fàbrega; Anna Aviñó; Ramon Eritja; Yoon-Sik Lee; Yogesh S. Sanghvi; Susana Fernández; Miguel Ferrero (Results in Chemistry)
A critical step in the manufacturing of oligonucleotides is the selection of ideal solid supports. Herein, we evaluate a hybrid core–shell solid support made of polystyrene and polyethyleneglycol, for the preparation of oligonucleotides using phosphoramidite chemistry. The results were compared with those obtained using conventional solid supports including controlled-pore glass and polystyrene NittoPhase®. The core–shell supports provided good yields when phosphoramidites were dissolved in dichloromethane. Automatic DNA synthesizer was used to prepare several oligonucleotides carrying natural phosphate, phosphorothioate linkages, lipid conjugates and mesyl phosphoramidate dimers in acceptable yields. This study represents the first reported use of core–shell particles for the synthesis of chemically modified oligonucleotide sequences of therapeutic significance.